Utilização do Framework Cynefin na Evolução da Maturidade de Processos em Desenvolvimento de Software como Serviço (SaaS) - Maia, Nayane; Longman, Daniel (Anais do Workshop Anual do MPS (WAMPS), 2024)
This paper explores the application of the Cynefin framework to guide the transition of a cloud software development department from a complex to a complicated scenario. The transition aims to increase operational efficiency, predictability, and scalability. Using Cynefin, areas of uncertainty were identified and subsequently systematized and replicated through specific methodologies. The introduction of rapid feedback questions, such as ”Hot or Cold?”, proved effective for dynamic adjustments, ensuring continuous alignment with strategic goals.